Effect of a Nutrition Intervention on Mediterranean Diet Adherence Among Firefighters: A Cluster Randomized Clinical Trial - Hershey, Maria Soledad; Chang, Chia-Rui; Sotos-Prieto, Mercedes; Fernandez-Montero, Alejandro; Cash, Sean B.; Christophi, Costas A.; Folta, Sara C.; Muegge, Carolyn M.; Kleinschmidt, Vanessa; Moffatt, Steven M.; Mozaffarian, Dariush; Kales, Stefanos N. (My University, 2023)
US firefighters are a working population at risk of chronic diseases, including obesity, cardiovascular disease, and cancer. This risk may be mitigated by a healthy diet.
Keywords: Cardiometabolic Risk Factors; Cardiovascular Diseases; Control Groups; Diet; Mediterranean; Female; Firefighters; Humans; Male; Middle Aged